Belgian guidelines for non-occupational HIV post-exposure prophylaxis 2017. Issue 4 (4th July 2018) - Libois, Agnès; Florence, Eric; Derdelinckx, Inge; Yombi, Jean Cyr; Henrard, Sophie; Uurlings, Françoise; Vandecasteele, Stefaan; Allard, Sabine D.; Demeester, Rémy; Van Wanzeele, Filip; Ausselet, Nathalie; De Wit, Stéphane
ABSTRACT: We present the updated Belgian guidelines for the use of non-occupational HIV post-exposure prophylaxis (NONOPEP). This document is inspired by UK guidelines 2015, adapted to the Belgian situation and approved by all AIDS reference centers in Belgium. When recommended, NONOPEP should be initiated as soon as possible, preferably within 24 h of exposure but can be offered up to 72 h. The duration of NONOPEP should be 28 days. These current guidelines include epidemiologic estimations, which can be used to calculate the risk of infection after a potential exposure and help to decide whether or not to start prophylaxis. We review which medications to use in the context of the last Belgian NONOPEP convention, provide a checklist for initial assessment, and make recommendations for monitoring individuals receiving NONOPEP.